Effect of ascorbic acid pre-treatment on the characteristics of fried breadfruit (Artocarpus altilis) chips. - Tadlas, Jo Hanzelle Del Cano
Breadfruit (Artocarpus altilis) or kolo is an underutilized fruit in the Philippines although it serves as a staple food in tropical areas including the Pacific islands. Kolo can be used in various stages of maturity and in different forms such as boiled, candied and fried, and consumed alone or in combination with other food. A drawback in its utilization is the formation of browning once peeled and exposed to air. To prevent browning, the peeled and cut kolo prepared for fried chips production were soaked in two concentrations (w/v) of ascorbic acid in water prior to frying. The treatments were: 1% (T1) and 2% (T2), and without ascorbic. (Tc). After soaking for 10 minutes, the off-white color of T1 and T2 were significantly lighter than Tc (P<.001). The anti-browning effect on the fried kolo was higher in T2 than in T1 and Tc. After frying for 5 minutes at 1620C, T1 and Tc did not significantly differ in color and crispness. Both treatments had significantly darker browning and higher than T2. T1 was the most preferred kolo chips (MPKC) based on color by Kramer?s Rank Sum test. Mann-Whitney U Test at 5% level of significance showed the moisture (3.5%), fat (50%), protein (1.27%), and carbohydrate (41.50%) content of the MPKC significantly higher than Tc, while ash (4%) and fiber (0.05%) were not significantly different. In fried kolo chips, browning in T2 was also less than in T1 and Tc. However, the panelist preferred T1 and TC with the darker brown fried kolo chips than T2 when assessed based on color. A ?bitter aftertaste? was perceived in Tc, indicating that ascorbic acid treatment had prevented the development of the bitter taste. General acceptability showed that the fried MPKC was moderately liked. Ascorbic acid treatment was able to prevent browning and bitterness in unfried and fried kolo.